Encapsulation of Rice Bran Oil (RBO) by Complex Coacervation Using Glutaraldehyde as Crosslinking Agent - Fadilah Fadilah; Elfira Diah Ayu Febriani; Elvina Kurniasari; Refanza Nurfikhri; Tiurmasi Saulina Sirait (Equilibrium Journal of Chemical Engineering, 2023)
Abstract. Rice bran is a significant by-product of the processing of rice, and rice bran oil (RBO) can be extracted from it to provide a very valuable product. It has a high smoke point but is less stable in the heating process. Further research is carried out to increase the stability of Rice Bran Oil in its utilization. Many environmentally friendly methods are being developed in storing and packaging food, including the application of microencapsulation. This study aims to determine the effect of the use of glutaraldehyde crosslinking agent on rice bran oil microencapsulation by utilizing the natural polymers of kappa carrageenan, glucomannan, and chitosan as encapsulants using the coacervation method. Microcapsules were analyzed for their encapsulation efficiency and yield and were characterized using Fourier Transform Infrared Spectrophotometer (FTIR), Scanning Electron Microscope (SEM), and Particle Size Analyzer (PSA). Results show that increasing the amount of glutaraldehyde tends to increase the yield and efficiency of encapsulation. A yield of 49.20% was obtained by adding 1 mL of glutaraldehyde with an encapsulation efficiency of 48.22%. All samples have irregular shapes and the surfaces were rough and folded. FTIR spectra show that all samples indicated the presence of RBO as well as other polymers used in the research: carrageenan, chitosan, and glucomannan.  The results of PSA show that particles are in micron size except for the addition of 1 mL glutaraldehyde.Keywords:Rice Bran Oil. Glutaraldehyde, Complex Coacervation